Critical point theory of symmetric functions and closed geodesics - Clapp, Mónica; Puppe, Dieter (Differential geometry and its applications, 1996)
We develop a version of equivariant critical point theory particularly adapted to finding closed geodesics by variational methods and use it to improve the known lower bounds for the number of “short” closed geodesics on some closed Riemannian manifolds.
Elektronische Reproduktion der Druck-Ausgabe 16. Februar 1999
Gesehen am 11.05.2023